Pyrethroid resistance in Culex pipiens mosquitoes - Scott, Jeffrey G.; Yoshimizu, Melissa Hardstone; Kasai, Shinji (Pesticide Biochemistry and Physiology, 2015)
•Pyrethroid insecticides are frequently used to control Culex pipiens mosquitoes.•High levels of pyrethroid resistance are found in larvae throughout the world.•Multiple Vssc mutations have been found in resistant strains.•Overexpression of CYP9M10 appears to be a mechanism of resistance globally. Mosquitoes within the Culex pipiens complex are widely distributed and important in the transmission of many human diseases. Insecticides, pyrethroids in particular, remain a mainstay for control of these important vectors. In this paper we review what is known about the levels, mechanisms and fitness costs of pyrethroid resistance in Cx. pipiens. Pyrethroid resistance in Cx. pipiens is a global problem, and resistance ratios of up to 7000-fold have been found in larvae of field collected mosquitoes. However, there is considerable variation between populations, indicating significant geographic heterogeneity of the resistance. The two major mechanisms of resistance to pyrethroids in Culex are mutations in Vssc (target site insensitivity) and overexpression of cytochrome P450(s) (increased detoxification). The most frequently reported Vssc mutation is L1014F (i.e. kdr), which has been found throughout the world. The L1014S mutation has been found in Cx. p. pallens from Japan and China, and in Cx. p. pipiens from China. The L1014C mutation has only been reported for Cx. p. pipens molestus from China and the V1016G mutation has only been reported from Saudi Arabia. Studies on the P450s of Cx. pipiens have identified several that are overexpressed (measured as transcript levels) in pyrethroid resistant strains. CYP9M10 is consistently overexpressed in pyrethroid resistant Cx. pipiens from at least seven countries, suggesting this P450 might be of global importance in resistance. Both CYP9M10-mediated pyrethroid resistance and kdr have fitness costs in the absence of insecticides under certain environmental conditions. Research needs and future directions are discussed.